Eficacia del paico (Chenopodium ambrosioides) como antihelmíntico de parásitos gastrointestinales en caninos de la fundación vida animal del municipio de Popayán (Cauca) (2023)
The research aimed to determine the efficacy of the ascaridol active component of paico (Chenopodium ambrosioides) as an anthelmintic in canines at the animal life foundation, located in Popayan, Cauca. A bibliographic review was made of the taxonomic characteristics of the paico (Chenopodium ambrosioides) and its pharmacological characteristics that are used 10 as a dewormer. Solutions were made at concentrations of 10% and 15% of this plant which was administered orally to canines of different age and sex, compared with a commercial dewormer based on ivermectin 0.025%, praziquantel 2.5%, pyrantel embonate 7.4%. This in order to publicize the benefits of this plant. In the first phase of the study, qualitative and quantitative tests were done to determine the type of parasite found in the 30 canines sampled. The parasites that were identified with flotation test were Ancylostoma spp, Trichuris spp, Toxocara spp. Canines that were positive for these parasites were given the McMaster quantitative test to determine the number of eggs per gram of fecal matter. The three treatments to which the canines were subjected, generated a reduction of parasite eggs present in one gram of fecal matter. Based on the results of Tukey's test we can determine that there is no significant difference between treatments 1, 2, and 3.